24th AIAA Applied Aerodynamics Conference 2006
DOI: 10.2514/6.2006-3469
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Comparison of Hyper-Elliptic Cambered Span (HECS) Wings with Conventional Configurations

Abstract: /πAe C p = wake static pressure coefficient, (P s -P ∞ ) /q C pt = wake total pressure coefficient, (P t -P ∞ ) /q e = span load efficiency q = dynamic pressure S = wing planform area U ∞ = freestream tunnel velocity Λ c/4 = quarter chord sweep angle Λ c/2 = half chord sweep angle Ω = vorticity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Despite the identified aerodynamic benefits of a joint-driven morphing wing, a major challenge for any bioinspired UAV is to design an efficient actuation mechanism that can realize the proposed benefits in practice. In the past, a non-planar wing design that was indirectly inspired by gulls, the HECS wing (discussed in the Introduction) was shown to yield minimal aerodynamic benefits when it was actively morphed into its furled configuration [41] despite promising rigid model results [20]. This emphasizes the multidisciplinary challenges associated with effective morphing wing design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the identified aerodynamic benefits of a joint-driven morphing wing, a major challenge for any bioinspired UAV is to design an efficient actuation mechanism that can realize the proposed benefits in practice. In the past, a non-planar wing design that was indirectly inspired by gulls, the HECS wing (discussed in the Introduction) was shown to yield minimal aerodynamic benefits when it was actively morphed into its furled configuration [41] despite promising rigid model results [20]. This emphasizes the multidisciplinary challenges associated with effective morphing wing design.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, traditional geometric properties including distributions of wing twist, sweep, dihedral and the final wingspan can be approximated as functions of the joint positions [5,18]. Further, these non-planar wing shapes likely have aerodynamic characteristics that differ from comparable planar wing aerodynamic theory [19], as highlighted by the Hyper Elliptical Cambered Span (HECS) wing inspired by gulls, which had improved aerodynamic efficiency (higher lift-to-drag ratio) compared to an equivalent planar wing [20].
Figure 1Gull wings inspired our analyses of how avian joint-driven wing morphing affects longitudinal aerodynamic control, stability and balance.
…”
Section: Introductionmentioning
confidence: 99%
“…Could spanwise camber lead to a second trade-off, one between stability and efficiency during avian gliding? It has been previously demonstrated that engineered wings with spanwise camber do have increased aerodynamic efficiency, but there is no empirical evidence of the effects on static pitch stability [11,27]. Coupling of stability and efficiency is well established for certain aircraft configurations, including box wings and flying wings [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…One type of wing morphing that may allow such a transition is a wing that adjusts the curvature along its span, known as spanwise camber. Spanwise camber has been found to adjust the pressure distribution of aircraft wings, and thus the location of the aerodynamic centre along the wing [11,12]. An iconic example of a bird with spanwise camber is the gull.…”
Section: Introductionmentioning
confidence: 99%
“…A gradient-based method which is well-suited for nonlinear structural minimisation problems with nonlinear inequality constraints is the method of moving asymptotes (MMA) (36) . In this method, the nonlinear optimi-wing (38) . The reason for folding down is that the induced drag is reduced by increasing the aspect ratio of the wing while reducing the increased root bending moment due to the winglet.…”
Section: Optimisation Formulationmentioning
confidence: 99%